Zmiany w spożyciu mięsa i ryb w gospodarstwach domowych w Polsce w latach 1988-1998 - Zajączkowska, Maria; Borowska, Agnieszka (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2001)
The changes in meat and fish consumption of Polish households during 1988-1998 were analysed in the paper. One of the positive tendencies in food consumption in Poland (when taking into account some aspects of the human health) is increasing consumption of poultry meat and decreasing consumption of beef. Unfortunately, the research results indicate that the consumption of dietetically harmful pork by Polish households has not changed in the analysed period. At the same time, both an increase in the consumption of fish processed products and a decrease in the consumption of fish were observed.